USE OF GIS TECHNOLOGIES AND SATELLITE DATA FOR GEOLOGICAL RESEARCH - Kayumov Odiljon Abduraufovich (Western European Studies, 2024)
This study examines the integration of Geographic Information Systems (GIS) and satellite data in geological research, highlighting its effectiveness in enhancing spatial accuracy, resource mapping, fault line detection, and environmental monitoring. Using machine learning algorithms, high-resolution satellite imagery, and temporal analysis, the research demonstrates improvements in predictive accuracy and risk assessment, especially for seismic activity and resource identification. The findings suggest that advancing AI and satellite technologies could further enhance predictive models and support sustainable geological research and resource management practices.
Keywords: GIS; satellite data; geological research